2020
DOI: 10.1177/1557988320903193
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the Medicaid Expansion in the Use of Preventive Health Care Services in California Men

Abstract: Men’s use of preventive care services may be constrained due to a number of factors including lack of health care insurance. California used the Medicaid expansion provisions of the Affordable Care Act (ACA) to enroll low-income men between the ages of 18 and 64 years in publicly funded health insurance. Most studies on the effect of the ACA on health care services have focused on racial/ethnic differences rather than gender. Data from the California Health Interview Survey for the 2015–2016 survey period were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…This study has some limitations. One potential limitation of this study is the geographic variability in the proportion of cancer cases captured in the NCDB . Furthermore, Commission on Cancer–accredited hospitals are more likely to be larger, academic, urban facilities that offer more cancer-related services, such as screening, chemotherapy, and radiation .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This study has some limitations. One potential limitation of this study is the geographic variability in the proportion of cancer cases captured in the NCDB . Furthermore, Commission on Cancer–accredited hospitals are more likely to be larger, academic, urban facilities that offer more cancer-related services, such as screening, chemotherapy, and radiation .…”
Section: Discussionmentioning
confidence: 99%
“… 61 , 62 , 63 , 64 , 65 In the years surrounding Medicaid expansion, the incidence of kidney cancer in the US was relatively unchanged. However, studies have shown that the Medicaid expansion was associated with increased preventive care visits 66 and increased outpatient visits. 67 Thus, there is a similar potential explanation wherein the increased access to care and resources afforded by Medicaid expansion may lead to increased incidental diagnosis at early stages when kidney cancer is still asymptomatic.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some of the preventive services covered under the ACA are blood pressure, diabetes, cholesterol tests, colorectal cancer screening, depression screening, HIV screening, diet counseling, and hepatitis B and C screening (Fox & Shaw, 2015). The ACA also provides for preventive care services without cost-sharing under Medicare and requires that states cover preventive services under Medicaid without any cost-sharing (Reynolds & Fisher, 2020).…”
Section: Introductionmentioning
confidence: 99%